Utilizing E-LKPD (Electronic Student Worksheets) to Enhance Students’ Descriptive Text Writing at Junior Secondary School - Muafiah, Nurul; Noni, Nurdin; Korompot, Chairil Anwar (Journal of Excellence in English Language Education, 2025)
The purpose of the study is to discover how positively students perceive the use of electronic student worksheets, or E-LKPD, in the instruction of descriptive text as well as the efficacy of this approach. A quasi-experimental design with a non-equivalent control design was used in the study. The population of this study was 7th-grade students from SMP Pergis Islam Ganra located in Ganra, Kel. Ganra, Kec, Ganra, Kab. Soppeng. The sample of the study was 40 students of two classes from the seventh grade of SMP PERGIS ISLAM GANRA students which were taken by using cluster random sampling.  The data were obtained through writing tests and questionnaires. The results of the hypothesis test proved a significant difference in post-test scores between the experimental and control classes, with a 2-tailed value of 0.000 (0.05), indicating that the alternative hypothesis (H1) was accepted and the null hypothesis (H0) was rejected. This confirms that teaching descriptive text at the junior secondary level using E-LKPD is an effective method of instruction. Utilizing E-LKPD in teaching descriptive text at junior secondary schools offers several benefits, including enhanced student engagement and motivation through interactive and digital formats, leading to improved learning outcomes. Additionally, E-LKPD facilitates personalized learning experiences, catering to diverse student needs while also improving students’ technological literacy.